Dimensions of parenting among mothers and fathers in relation to social anxiety among female adolescents. (22nd July 2017) - Bynion, Teah‐Marie; Blumenthal, Heidemarie; Bilsky, Sarah A.; Cloutier, Renee M.; Leen‐Feldner, Ellen W.
ABSTRACT: Social anxiety is the most common anxiety disorder among youth; theoretical and empirical work suggest specific parenting behaviors may be relevant. However, findings are inconsistent, particularly in terms of maternal as compared to paternal effects. In the current study, we evaluated the indirect effects of perceived psychological control on the relation between anxious rearing behaviors and child social anxiety among 112 community‐recruited girls (ages 12–15 years). In addition to self‐report, adolescent participants completed a laboratory‐based social stress task. In line with hypotheses, results indicated indirect effects of psychological control on the relation between anxious rearing behaviors and child social anxiety in maternal but not paternal models. Findings are discussed in terms of their theoretical and empirical implications for clarifying the role of parental relations in adolescent social anxiety.